Olivia Sharp : The Green Toenails Gang - Sharmat, Marjorie Weinman; Sharmat, Mitchell; Brunkus, Denise (New York : Yearling, 2005)
Wealthy Olivia Sharp, agent for secrets, uncovers several secrets on a trip to Carmel, California to help a friend become a member of an exclusive club.
"A Yearling Book."
2.0.
006-009.
Keywords: Secrets -- Fiction; Clubs -- Fiction; Friendship -- Fiction